Caracterização de novos peptídeos selecionados por Phage Display como ligantes a células tumorais mamárias - Martins, Isabella Castro (2022)
Breast Cancer (BC) is the most frequently diagnosed tumor worldwide and one of the leading causes of death among women. Early diagnosis and effective therapies, especially targeted-therapy, are essential for patient survival, requiring molecular characterization of tumors. The Phage Display (PD) technique is a versatile tool that allows the selection of potentially theranostic bioactive peptides. In this context, the present study aimed to validate the chemically synthesized peptides C3 and H2, previously selected by our group by PD, regarding their ability to recognize and bind to mammary cell lines MCF-10A (non-tumorigenic), MCF-7 (luminal BC), MDA-MB231 (triple-negative BC) and their potential use in drug delivery. The staining assays, by immunofluorescence and flow cytometry, showed that both, especially the C3 peptide, have specificity to tumor cells, especially to the luminal phenotype. A viability assay showed that, after treatment with the peptides, it was maintained above 90% in MCF-10A and MDA-MB231 cells, being slightly more cytotoxic to MCF-7 at higher concentrations, corroborating its targeting to the luminal subtype of BC. In peripheral blood mononuclear cells (PBMCs), we observed that cell viability was maintained at all concentrations. Finally, IL-6 levels were also evaluated by ELISA and no C3 peptide-mediated immune modulation was observed. Therefore, our results suggest that the peptides recognize breast tumor cells, not activating pro-tumorigenic mechanisms through the cytokine IL-6, which makes them potentially applicable for delivering drugs to luminal breast tumors.